Building information modeling : applications and practices - Issa, Raymond; Olbina, Svetlana (American Society of Civil Engineers, 2015)
This book contains 13 chapters, contributed by international researchers and practitioners, that present a comprehensive overview of the recent advances in the application of BIM across the AECO industry. The use of BIM is examined as a framework for structural design; in cost estimation; in adaptive cyber-physical systems; in construction progress monitoring and project management; in green building project delivery; in commissioning and facilities management; in military construction; in model assessment; and in integration with augmented reality. --